43a-27=14

Simple and best practice solution for 43a-27=14 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 43a-27=14 equation:


Simplifying
43a + -27 = 14

Reorder the terms:
-27 + 43a = 14

Solving
-27 + 43a = 14

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '27' to each side of the equation.
-27 + 27 + 43a = 14 + 27

Combine like terms: -27 + 27 = 0
0 + 43a = 14 + 27
43a = 14 + 27

Combine like terms: 14 + 27 = 41
43a = 41

Divide each side by '43'.
a = 0.9534883721

Simplifying
a = 0.9534883721

See similar equations:

| 3x+5=87 | | (y+4)(y+5)=0 | | a/2-3=-10 | | r-58=54 | | -14/2-3=-10 | | -2n-4(n+8)=4n-12 | | 2x^2+75=0 | | -144=4x^4-64x^3+254x^2-2x | | 90+c=19 | | 2x/6-4x+8/4=7 | | 7+u=-69 | | 2y+3x-12=0 | | y-(-7)=(-5/6)(x-7) | | -71+u=11 | | 6y-3=9y | | 5(P-8)=P+3 | | -8(x+6)=6v-34 | | (-5/6)(x-7) | | w-69=-63 | | 4x+80=50x-12 | | 7=32+b | | -19-6k=6(1+3k) | | 2,3f+12=40 | | 6x^9/x^2 | | 17x-3=9x+13 | | 49x^2-56+16= | | 3t^2-24t+45=0 | | 4p+12= | | (N+4)*3=36 | | 6x+2=3x+7 | | A/6-1=7 | | 11=r/13 |

Equations solver categories